(untitled) (Research, Society and Development, 2020)
Science classrooms are formal and privileged spaces, ideal for spreading scientific knowledge, problematizing situations and promoting meaningful learning. Research teaching helps to change and/or build the student’s conceptual profile, and its methodologies allow him to be the protagonist of his learning. This work deals with the successful experience and the results obtained when using the resource ’comics’ as a way to systematize concepts learned, in Chemistry, with students of the second year of high school in a state school in Piracicaba. An investigative didactic sequence was applied to introduce the content of acidity and basicity of solutions, divided into four classes. The results obtained were satisfactory considering that the students had no previous contact with the content. The investigative sequence contributed to the construction of solid concepts related to the topic addressed. Based on the results, it was clear that the use of comics contributed to the systematization of concepts, stimulating the desire to research linked to the awakening of scientific knowledge, as well as teamwork.